Operasional Badan Amil Zakat Nasional (Baznas) Dalam Penghimpunan serta Penyaluran Dana Zakat di Kota Pematangsiantar - Tryana Ramadhany Batubara; Muhammad Syahbudi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine the operations of the National Amil Zakat Agency (BAZNAS) in collecting and distributing zakat funds in Pematangsiantar City. This research method uses two approaches, namely quantitative and qualitative approaches. The results of this study indicate that the distribution of zakat funds at the Pematangsiantar BAZNAS office is still in the nature of distributing zakat funds in a consumptive way, namely zakat funds given to mustahiq to be used in meeting the necessities of life as is the case with clothing, food and so on. And these consumptive zakat funds cannot be used as productive zakat funds or the development of zakat funds by means of business, for example, they are only used to fulfill basic needs in daily life. Supporters and obstacles in the collection and distribution of zakat funds are still lacking in facilities, both facilities and human resources who are ready to pick up donors and look for donors, then there is still a lack of awareness of muzakki in fulfilling their zakat obligations. Keywords: BAZNAS, Collection, Distribution and Operations